Clinical and hormonal findings in patients presenting with high IGF-1 and growth hormone suppression after oral glucose load: a retrospective cohort study. Issue 2 (1st July 2021) - Carosi, Giulia; Mangone, Alessandra; Sala, Elisa; Del Sindaco, Giulia; Mungari, Roberta; Cremaschi, Arianna; Ferrante, Emanuele; Arosio, Maura; Mantovani, Giovanna
Abstract : Objective: High insulin-like growth factor 1 (IGF-1) and unsuppressed growth hormone (GH) levels after glucose load confirm the diagnosis of acromegaly. Management of patients with conflicting results could be challenging. Our aim was to evaluate the clinical and hormonal evolution over a long follow-up in patients with high IGF-1 but normal GH nadir (GHn < 0.4 μg/L according to the latest guidelines). Design: Retrospective cohort study. Methods: We enrolled 53 patients presenting high IGF-1 and GHn < 0.4 μg/L, assessed because of clinical suspicion of acromegaly or in other endocrinological contexts (e.g. pituitary incidentaloma). Clinical and hormonal data collected at the first and last visit were analyzed. Results: At the first evaluation, the mean age was 54.1 ± 15.4 years, 34/53 were females, median IGF-1 and GHn were +3.1 SDS and 0.06 μg/L, respectively. In the whole group, over a median time of 6 years, IGF-1 and GHn levels did not significantly change (IGF-1 mean of differences: −0.58, P = 0.15; GHn +0.03, P = 0.29). In patients with clinical features of acromegaly, the prevalence of acromegalic comorbidities was higher than in the others (median of 3 vs 1 comorbidities per patient, P = 0.005), especially malignancies (36% vs 6%, P = 0.03), and the clinical worsening overtime was more pronounced (4 vs 1 comorbidities at the last visit). Conclusions: In patients presenting high IGF-1 but GHn < 0.4 μg/L, a hormonal progression is improbable, likely excluding classical acromegaly in its early stage. However, despite persistently low GH nadir values, patients with acromegalic features present more acromegalic comorbidities whose rate increases over time. Close clinical surveillance of this group is advised.